Water soluble lanthanoid benzoate complexes for the kinetic separation of cis/trans-limonene oxide - Andrews, P.; Blair, M.; Fraser, B.; Junk, P.; Massi, Massimiliano; Tuck, K. (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2006)
A new class of water soluble, environmentally friendly, lanthanoid 3,5-diacetamidobenzoate complexes (Ln = La, Gd, Yb) have been synthesized. The La and Gd complexes selectively catalyse hydrolysis of the cis-isomer of limonene oxide allowing for the separation of the trans-isomer (> 98:2 dr) in up to 74% yield. Comparative studies with the corresponding chlorides and triflates reveal the lanthanoid benzoate complexes to be more active than the chlorides, but less active, though more selective, than the triflates